Konsep Tadabbur dalam Khawatir Asy-Sya'rawi - Arsyad Ridho Sibyan; Muhammad Amrulloh; Indriastuti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines Imam Asy-Sya‘rawi’s concept of tadabbur in his Tafsîr Khawâtir, addressing the widespread belief that understanding the Qur’an requires advanced scholarly authority and the societal tendency to judge others rather than engage in self-reflection.. By focusing on four key verses where the command for tadabbur appears (An-Nisa’ 82, Al-Mu’minun 68, Muhammad 24, and Shad 29), this paper outlines Asy-Sya‘rawi’s distinctive interpretive method that links rational inquiry, spiritual receptivity, and social awareness. Employing a qualitative-descriptive approach with a thematic tafsir method, this library research draws upon Tafsîr Khawâtir Asy-Sya‘rawî as the primary source, alongside secondary literature to contextualize his views within broader Qur’anic exegesis. The study reveals that tadabbur is not only a Qur’anic imperative but also as demonstrated in Asy-Sya‘rawi’s emphasis on spiritual sincerity, daily reflection, and ethical behavior. This study contributes to Qur’anic hermeneutics by highlighting a synthesis of spirituality, rationality, and thematic reflection in modern tafsir tradition.